EDITORIAL: Pacific media advocacy - David Robie (Asia Pacific Network, 2017)
IN SAMOA during July 2015, a new Pacific journalism education and training advocacy era was born with the establishment of the Media Educators Pacific (MEP) after a talkfest had gone on for years about the need for such a body. A draft constitution had even been floated at a journalism education conference hosted at the University of the South Pacific in 2012. The initiative created unity of sorts between the Technical, Vocational and Educational Training (TVET) media institutes from Fiji, Samoa, Solomon Islands and Vanuatu, and the regional University of the South Pacific journalism programme. Founding president Misa Vicky Lepou of the National University of Samoa pledged at the time to produce a vision with a difference: